Comparison of Sedation Scores with Different Doses of Propofol in Spinal Anesthesia - Yiğit, Hilal; Erbüyün, Koray; Tok, Demet; Ok, Gülay; Tekin, İdil (Fırat University, 2006)
Objective: The depth of sedation produced by 3 different infusion doses of propofol was compared by means of Observer Assessment of Alertness and Sedation Scores(OAA/S) and Bispektral Indeks (BIS) during spinal anesthesia. Materials and methods: With the permission of hospital ethics committee, 18-60 year old 60 patients in ASA I-III who would undergo spinal anesthesia were divided into 3 groups, randomly. Following spinal anesthesia, 1mg.kg-1 propofol bolus was given to all patients intravenously and then, a continuous infusion of propofol, 3mg.kg-1.h-1 in GroupI, 4mg.kg-1.h-1 in GroupII and 5mg.kg-1.h-1 in GroupIII were started. Heart rate(HR), mean arterial pressure(MAP), perypheral oxygen saturation(SpO2), respiration rate(RR), BIS, OAA/S were recorded before propofol infusion and during 45min. with intervals of 5min after infusion. Side effects and complications were observed during infusion. Results: OAA/S and BIS were significantly lower than basal values at all measurements in all groups. In GroupI, OAA/S was significantly higher at 20thmin than the other groups. In GroupIII, OAA/S at 15th min was lower than the other groups. Even the decreases at HR, MAP, RR and SpO2 were observed, there had been no important cardiovascular or ventilatory depression requiring either to stop infusion or urgent therapy. Conclusion: Considering OAA/S values, 3mg.kg-1.h-1 propofol dose was found to reach the optimum sedation level in the highest ratio without any adverse effects. Besides, 4 and 5mg.kg-1.h-1 dose of propofol maintained deeper sedation without any adverse effects.©2006, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Bu çalışmanın amacı, spinal anestezi sırasında, propofolün 3 farklı dozuyla yapılan sedasyon derinliğinin, Observer Assessment of Alertness and Sedation Scale (OAA/S) ve Bispektral Indeks (BİS) kullanarak karşılaştırılması idi. Ayrıca optimum sedasyon düzeyini sağlayan en uygun propofol dozu ve yan etkileri araştırıldı. Gereç ve yöntem: Hastane etik kurulu onayıyla 18-60 yaş aralığında, spinal anestezi planlanan 60 hasta rasgele 3 gruba ayrıldı. Spinal anestezi uygulandıktan sonra tüm hastalara 1mg.kg.-1 propofol iv bolus olarak verildi. Daha sonra GrupI’e 3mg.kg-1.sa-1, GrupII’ye 4mg.kg-1.sa-1 ve GrupIII’e 5mg.kg-1.sa-1 olacak şekilde propofol infüzyonuna başlandı. Kalp atım hızı (KAH), ortalama arter basıncı (OAB), periferik O2 satürasyonu (SpO2), solunum sayısı (SS), BİS ve OAA/S değerleri, propofol infüzyonundan önce ve 45 dakika infüzyon boyunca her 5 dakikada bir kaydedildi. İstenmeyen etkiler ve komplikasyonlar kaydedildi. Bulgular: OAA/S ve BİS değerleri bütün gruplarda, tüm ölçümlerde, kontrol değerine göre anlamlı oranlarda azaldı. OAA/S değerleri 20. dk.’dan itibaren tüm ölçümlerde Grup I’ de diğer gruplara oranla anlamlı oranda yüksek bulundu Grup III’ de 15.dk diğer gruplardan anlamlı oranda düşük bulundu. KAH, OAB, SS ve SpO2 zaman zaman azalsa da hiçbir olguda infüzyonu sonlandırmak veya acil tedaviyi gerektiren önemli kardiyovasküler veya solunum depresyonu görülmedi. Sonuç: OAA/S’nin optimum değerlerine ulaşmak için 3mg.kg-1.sa-1dozunda propofol infüzyonun yeterli olduğu ve istenmeyen etkilerin görülmediği izlenmiştir. Yanı sıra, 4 ve 5mg.kg-1.sa-1 propofol infüzyon dozlarıyla daha derin sedasyon olursa da, bu dozlarda da istenmeyen etki görülmemiştir.©2006, Fırat Üniversitesi, Tıp Fakültesi
Spinal Anestezide Farklı Dozlardaki Propofol Sedasyonunun Karşılaştırılması